Simplifying and Isolating Failure-Inducing Input: A Retrospective on Delta Debugging - Zeller, Andreas; Hildebrandt, Ralf (IEEE transactions on software engineering, 2025)
Delta Debugging is a technique to simplify and isolate failure-inducing changes. Its most popular application is on program inputs, where it reduces a failure-inducing input to a minimal input that still triggers the failure. This paper provides a retrospective on Delta Debugging, discussing its origins, applications, and impact. We also discuss the limitations of Delta Debugging and suggest directions for future research.